2019
DOI: 10.18632/oncotarget.26745
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Krüppel-Like Factor 4 (KLF4) expression through the transcription factor Yin-Yang 1 (YY1) in non-Hodgkin B-cell lymphoma

Abstract: Krüppel-Like Factor 4 (KLF4) is a member of the KLF transcription factor family, and evidence suggests that KLF4 is either an oncogene or a tumor suppressor. The regulatory mechanism underlying KLF4 expression in cancer, and specifically in lymphoma, is still not understood. Bioinformatics analysis revealed two YY1 putative binding sites in the KLF4 promoter region (-950 bp and -105 bp). Here, the potential regulation of KLF4 by YY1 in NHL was analyzed. Mutation of the putative YY1 binding sites in a previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Recent studies by our group have shown that the expression of the KLF4 in lymphoma plays a pro-tumoral role and that it correlates with malignancy (14). Likewise, our working group and other groups have reported that the transcription factor YY1 is expressed in high levels in lymphomas, and we recently reported that this transcription factor regulates the expression of KLF4 in lymphoma cell lines (15). Because of this, in this study, we analyzed the possible role of miR-7 in lymphomagenesis by regulating YY1 and KLF4 in NHL.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…Recent studies by our group have shown that the expression of the KLF4 in lymphoma plays a pro-tumoral role and that it correlates with malignancy (14). Likewise, our working group and other groups have reported that the transcription factor YY1 is expressed in high levels in lymphomas, and we recently reported that this transcription factor regulates the expression of KLF4 in lymphoma cell lines (15). Because of this, in this study, we analyzed the possible role of miR-7 in lymphomagenesis by regulating YY1 and KLF4 in NHL.…”
Section: Introductionmentioning
confidence: 52%
“…Biopsies from patients diagnosed with NHL were fixed in triplicate in a tissue microarray. Hematoxylin/Eosin (H&E) stains were made for an expert pathologist to select areas representative of the tumor, as previously reported, and new slides from same TMA previously reported were used in this work (15). Same samples of patients are included, but new stains and images were made for this study.…”
Section: Tissue Microarray (Tmas)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the disorders that have reportedly resulted from KLF4 gene-related diseases include secretory meningioma, cerebral cavernous malformations, skin squamous cell carcinoma, germ cell, embryonal cancer, and familial adenomatous polyposis(Morales-Martinez et al, 2019).Herein, we demonstrate the upregulation of KLF4 gene in A. dichotoma hemolymph-treated INS-1 pancreatic β-cells.The gene expression of KLF4 is significantly up regulated in transcriptional level from our previous cDNA microarray experiment. Hemolymph exposure in INS-1 cells for 2 h resulted in 7.06-folds increase in KLF4 levels as compared to the control genes.…”
mentioning
confidence: 65%
“…Moreover, it has also been demonstrated that pRb- YY1 interaction prevents YY1 binding to the c-Myc promoter in normal B cells, but not in BL cells [ 13 ]. Finally, YY1 may positively regulate the expression of another transcription factor KLF4, showing a dual role in cancer, with a possible prognostic value [ 42 ]. Altogether, these findings suggest that the molecular context and the molecular players available (including surrounding co-activators and co-repressors) may highly influence the final outcome of YY1 transcriptional activity, which can be very heterogeneous.…”
Section: Discussionmentioning
confidence: 99%